Question
upstudy study bank question image url

\( \left(10 x^{2}-9\right)^{\frac{1}{4}}=x \) What is the sum of the solutions to the given equation?

Ask by Bowman Olson. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The sum of the solutions is 4.

Solution

To solve the equation \( \left(10 x^{2}-9\right)^{\frac{1}{4}} = x \), follow these steps: 1. **Raise Both Sides to the Fourth Power**: \[ 10x^2 - 9 = x^4 \] 2. **Rearrange the Equation**: \[ x^4 - 10x^2 + 9 = 0 \] 3. **Solve the Biquadratic Equation**: Let \( y = x^2 \), the equation becomes: \[ y^2 - 10y + 9 = 0 \] Using the quadratic formula: \[ y = \frac{10 \pm \sqrt{100 - 36}}{2} = \frac{10 \pm 8}{2} \] Thus, \( y = 9 \) or \( y = 1 \). 4. **Find \( x \) from \( y \)**: - If \( y = 9 \), then \( x = \pm 3 \). - If \( y = 1 \), then \( x = \pm 1 \). 5. **Check for Valid Solutions in the Original Equation**: - **\( x = 3 \)**: \[ \left(10(3)^2 - 9\right)^{1/4} = \left(90 - 9\right)^{1/4} = 81^{1/4} = 3 \quad \text{(Valid)} \] - **\( x = -3 \)**: \[ \left(10(3)^2 - 9\right)^{1/4} = 81^{1/4} = 3 \neq -3 \quad \text{(Invalid)} \] - **\( x = 1 \)**: \[ \left(10(1)^2 - 9\right)^{1/4} = 1^{1/4} = 1 \quad \text{(Valid)} \] - **\( x = -1 \)**: \[ \left(10(1)^2 - 9\right)^{1/4} = 1^{1/4} = 1 \neq -1 \quad \text{(Invalid)} \] Therefore, the valid solutions are \( x = 3 \) and \( x = 1 \). 6. **Sum of the Solutions**: \[ 3 + 1 = 4 \] **Answer:** 4

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \( \left(10 x^{2}-9\right)^{\frac{1}{4}}=x \), we begin by raising both sides to the power of 4 to eliminate the fourth root: \[ 10x^2 - 9 = x^4 \] Rearranging the equation yields: \[ x^4 - 10x^2 + 9 = 0 \] Next, we can make a substitution to simplify this quartic equation. Let \( y = x^2 \). This transforms our equation into a quadratic form: \[ y^2 - 10y + 9 = 0 \] Now, we will factor this quadratic. We look for two numbers that multiply to \( 9 \) and add to \( -10 \). Those numbers are \( -1 \) and \( -9 \). Thus, we can factor it as: \[ (y - 1)(y - 9) = 0 \] Setting each factor to zero gives us the solutions for \( y \): \[ y - 1 = 0 \quad \Rightarrow \quad y = 1 \] \[ y - 9 = 0 \quad \Rightarrow \quad y = 9 \] Recalling that \( y = x^2 \), we substitute back: 1. From \( y = 1 \): \[ x^2 = 1 \quad \Rightarrow \quad x = 1 \quad \text{or} \quad x = -1 \] 2. From \( y = 9 \): \[ x^2 = 9 \quad \Rightarrow \quad x = 3 \quad \text{or} \quad x = -3 \] Thus, the solutions for \( x \) are \( 1, -1, 3, \) and \( -3 \). Next, we find the sum of all these solutions: \[ 1 + (-1) + 3 + (-3) = 0 \] Therefore, the sum of the solutions to the equation is: \[ \boxed{0} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy